O jornal A Imprensa e o cinema sob o olhar da Igreja Católica paraibana (1936-1942) - Ramos Neto, Luiz Araújo (2021)
This work aims to analyze and understand the project developed by the Archdiocese of the State of Paraíba, in relation to cinema, having as its main focus the discourse produced by its official press, the newspaper A Imprensa between the years 1936 and 1945 regarding the seventh art. To contemplate this objective, the discussion about modernity in the then City of Parahyba (currently João Pessoa) was undertaken, through two fundamental instances that arise in the context of urbanization and modernization of the capital; the newspaper A Imprensa, owned by the Catholic Church in Paraíba, and cinema, from its arrival to the professionalization process in the fields of exhibitor and producer. After completing this discussion, a broad analysis of the newspaper A Imprensa was carried out between the years 1936 and 1942, starting from the structure of the newspaper, discussing its conflicts in the political field, and ending with an analysis of the publication of the encyclical Vigilanti Cura in 1936, contextualizing with the action of Catholic groups that, in the international and national spheres, made efforts to establish a moral censorship for the audiovisual. The analysis was carried out through the precepts established by the theoretical framework of Cultural History, estrablishing, from the trajectory of the printed operation, the social place of the individuals involved with its production, the intentions and existing representations, the political culture that guided it and the multiple meanings and appropriations made by the readership, to whom this publication was destined. Finally, an analysis of the segment destined by the newspaper for the discussion of the audiovisual between the years 1937 and 1945 was undertaken, a section that centralized the discussions carried out in relation to the moralizing project defended by the Archdiocese of the State of Paraíba for the cinema. The sources used in this dissertation consist of volumes of the newspaper A Imprensa, which are found in the Ecclesiastical Archive of the Archdiocese of Paraíba.